EFFECT OF OUTER MEMBRANE VESICLE PROTEINS OF XENORHABDUS BACTERIA AGAINST MALARIAL VECTORS - VANI C,; LALITHAMBIKA B, (International Journal of Pharma and Bio Sciences, 2014)
Native Xenorhabdus Sp was isolated from the Entomopathogenic Nematodes Steinernema Sp used as a biopesticide for the control of malarial vectors. The Xenorhabdus bacterium which is symbiotically associated with Steinernema Sp has a wider range of toxic proteins secreted in the medium. Most of the protein secreted by the bacteria are extra cellular proteins of the Outer Membrane Vesicles (OMVs) of this gram negative bacteria plays an important role in killing the host larvae. The molecular weight of the OMV proteins of the isolates of Xenorhabdus Sp ranges from 20-97 KDa. This bacterium is proved to be an insect pathogen with an excellent source of insecticidal agents of proven toxicity. The outer membrane vesicles of this bacteria act as natural bombs by transporting virulence factors into the host. The novel approach of our present study includes the biopesticidal approach of the OMVs proteins from the isolated strains of Xenorhabdus Sp from the sugarcane fields in Tamilnadu against third instar Anopheles gambiae mosquito larvae, which transmits Plasmodium causes a major infectious disease called Malaria.100 ng/ml of OMV protein treated against the larvae recorded maximum mortality (93.32%) with the isolates XBS21 and XNHS 12 (76%). This was the first report showing the biopesticidal property of the OMV proteins of the isolates of Xenorhabdus Sp against the malarial vectors.